Anti-glycating and anti-oxidant compounds from traditionally used anti-diabetic plant Geigeria alata(DC) Oliv. & Hiern. Issue 17 (1st September 2020) - Fadul, Eltayeb; Nizamani, Arsalan; Rasheed, Saima; Adhikari, Achyut; Yousuf, Sammer; Parveen, Shahida; Gören, Nezhun; Alhazmi, Hassan A.; Choudhary, M. Iqbal; Khalid, Asaad
Abstract: A new sesquiterpene lactone geigerianoloide (1 ) and four known flavonoids axillarin (2 ), quercetin (3 ), 3-methoxy-5, 7, 3', 4'-tetrahydroxy-flavone (4 ) and hispidulin (5 ) were isolated from Geigeria alata (DC) Oliv. & Hiern. (Asteraceae). Structures were deduced using 1 H- and 13 C- NMR spectroscopy, mass spectrometry, while the structure of compound 1 was also deduced using X-ray crystallography technique. Geigeria alata is traditionally used for diabetes, therefore compounds were tested for anti-glycation activity, in which compounds 2 and 3 showed potent activities (IC50 values of 246.97 ± 0.83 and 262.37 ± 0.22 µ M, respectively) compared to IC50 value 294.50 ± 1.5 µ M of rutin. Moreover, compound 4 exhibited a comparable activity to rutin (IC50  = 293.28 ± 1.34 µ M). Compound 5 showed a weak activity. Compounds 2, 3, and 4 exhibited potent DPPH radical scavenging activity (IC50  = 0.1 ± 0.00, 0.13 ± 0.00 and 0.15 ± 0.01 µ M, respectively). Compounds 2, 3, and 4 demonstrated significant superoxide anion scavenging activity with IC50 values of 0.14 ± 0.001, 0.17 ± 0.00, and 0.11 ± 0.006 µ M, respectively. Abstract :